Cognitive Structure Trajectory in Developing Limit Concept Learning in Senior High School - Simin Simin; Mohamad Rif'at; Evi Noviani (AL-ISHLAH: Jurnal Pendidikan, 2023)
The existing comprehension of the concept of limit is marked by a deficiency in prioritising the enhancement of students' cognitive frameworks. The aim of this study is to examine the formation of cognitive structures while acquiring the concept of limitations. This study utilises qualitative approaches, namely descriptive analysis, to examine the development of cognitive processes in the process of acquiring the concept of boundaries. This study investigates the investigation of cognitive structures to ascertain the process of drawing conclusions, with the aim of creating instructional materials that facilitate comprehension of the concept of constraints. The survey included students who were currently enrolled in the 2021/2022 academic year at three public senior high schools in Pontianak. The study aims to analyse the progression of students' cognitive structures during the acquisition of the concept of limitations. The results revealed that all 14 students showed competence in determining the limit of a continuous polynomial function, specifically in the context of a linear function and a quadratic function. Substitution is commonly used to determine the limit of a linear function and the limit of a quadratic function. Only a single student employs the attributes of the limit function and graph trajectory to solve these two categories of problems. Researchers can conduct further investigation to examine the misconceptions that students have regarding the limit of functions. These misconceptions can be detected by analysing problems that involve substitution and have solutions that are already known. In senior high school, it is advisable to use graphs and tables to teach the concept of limit function since they aid in facilitating the learning process.